Uthman Ibn Affan : His Life & Time - Ali M. Sallabi, Dr.; Translated by Hamalainen, Rashid (Riyadh International Islamic Publishing House, 2013)
Islamic Empire; history, 622-661.
Include Glossary and Index
Keywords: Biography